A new remarkable species of Xyletinus Latreille, 1809 (Coleoptera: Ptinidae: Xyletininae) from southern Kazakhstan - Kovalev, Alexey V.; Shapovalov, Andrey M.; Smirnov, Maxim E. (Zootaxa, 2024)
Xyletinus (Xeronthobius) diaphanus sp. n. from southern Kazakhstan is described, illustrated, and compared with the known members of the subgenus.